Contesting Communalism(s): Preliminary Reflections on Pasmanda Muslim Narratives from North India - Ansari, Khalid Anis (Prabuddha: Journal of Social Equality; Vol 1 No 1 (2018), 2018)
The purpose of this study is not to contribute directly to questions of why, how or what of communalism but rather to employ the extant body of knowledge to represent and interpret the articulations advanced by activists associated with the Pasmanda movement—a movement of subordinated caste Muslims in India. The movement aspires to organize various subordinated Muslim castes, which form about eighty percent of India’s largest Muslim minority, in order to challenge the hegemony of the high caste ashrāf or sharīf Muslims. The Pasmanda movement has complicated the politics around Islam and Muslim (minority) identity, which has been seen as monolithic in public discourse. The movement, claiming to represent the concerns of Bahujan Muslims drawn mostly from the artisan or working-class background, has challenged the fascination of old Muslim elite with cultural and symbolic issues. In marked contrast, the Pasmanda activists have foregrounded organic social issues related to everyday struggles for survival thereby creating a new counterhegemonic discursive space.